In vitro study of AFB1 and AFM1 effects on human lymphoblastoid Jurkat T-cell model. (October 2014) - Luongo, D.; Russo, R.; Balestrieri, A.; Marzocco, S.; Bergamo, P.; Severino, L.
Abstract Aflatoxin B1 (AFB1) is a mycotoxin produced by Aspergillus spp. that can occur as a natural contaminant in foods and feeds of vegetable origin. Post-ingestion, AFB1 can be metabolized in the liver of mammals into hydroxylated aflatoxin M1 (AFM1) that is excreted with milk. Although several studies have been carried out to evaluate effects of AFB1 on the immune system, studies regarding AFM1 are moreover lacking. The aim of the current study was to investigate effects of AFB1 and AFM1 on immune function using a lymphoblastoid Jurkat T-cell line as an experimental model. Both AFB1 and AFM1 produced significant decreases in Jurkat cell proliferation, whereas only minor effects were noted on interleukin (IL)-2 and interferon (IFN)-γ cytokines mRNA expression in stimulated cells that had been pre-incubated with AFB1 and AFM1. Particularly, AFB1, but not AFM1, at the highest concentration (50 µM) induced a marked increase in IL-8 mRNA expression. The results of the current study suggested the existence of a concentration threshold for AFB1 and AFM1 needed to exert biological activity on cell viability and innate immunity.